2016
DOI: 10.2147/ccid.s76088
|View full text |Cite
|
Sign up to set email alerts
|

The psychosocial impact of acne, vitiligo, and psoriasis: a review

Abstract: IntroductionChronic skin conditions have been well reported to affect a patient’s quality of life on multiple dimensions, including the psychosocial domain. Psychosocial is defined as the interrelation of social factors with an individual’s thoughts and behavior. The assessment of the psychosocial impact of skin disease on a patient can help direct the dermatologists’ treatment goals. To evaluate the psychosocial impact of skin disease, we conducted a review of the literature on three skin conditions with onse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 34 publications
1
53
0
5
Order By: Relevance
“…Psoriasis has shown a marked upward trend in recent years. The course of psoriasis is comparatively long and recurrence happens frequently, which seriously affects patients' quality of life, causing great harm to their physical and mental health [4]. To date, there is no cure for psoriasis, mainly because its exact etiology and pathogenesis have not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Psoriasis has shown a marked upward trend in recent years. The course of psoriasis is comparatively long and recurrence happens frequently, which seriously affects patients' quality of life, causing great harm to their physical and mental health [4]. To date, there is no cure for psoriasis, mainly because its exact etiology and pathogenesis have not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…encontraron que el acné facial causa incremento de los niveles de ansiedad social, depresión y deterioro de la calidad de vida (19). Nguyen encontró que el acné provoca un aumento de la ansiedad y depresión en su población de estudio de estudio (20). La discrepancia se explica por los diferentes enfoques psicosociales que se presentan conforme avance la edad de la persona.…”
Section: Discussionunclassified
“…in photos, under a bright light, up close), as well as difference in colour between the skin and scar. The ACNE‐Q also measures appearance‐related distress, which is important because it has been found that acne has a negative impact on psychosocial function . In a recent systematic review that examined the effect of acne treatment on HRQoL, 37 studies were identified that used a variety of instruments, including both generic and disease‐specific ones.…”
Section: Discussionmentioning
confidence: 99%